A territorialização da agroindústria canavieira em Cachoeira Dourada (GO) e as transformações socioespaciais - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The changes by which the sugarcane agroindustry passed in its long period of production in Brazil reflected directly in the organization of the territory, either in the colonial period with the sugar economy or more recently with the production of energy provided by sugarcane. The productive restructuring of the sugarcane industry, based on technological innovations and normative and new spatialisation of the production of sugar, ethanol and energy, define the industry in the 21st century. The set of natural viabilities, political and economic conditions favored the expansion process of the Brazilian sugarcane energy sector by the areas of the Cerrado. The state of Goias became prominent, being responsible for redesigning the geography of production and the expansion of cultivation. In this context, the municipality of Cachoeira Dourada falls within the territory of the sugar-cane through the territorialisation of Group SJC Bioenergy through the Usina Rio Dourado. Thus, the present study aimed to understand the factors that contributed to the territorialisation of group SJC in Cachoeira Dourada, the strategies used by the group to exercise the monopolisation of the territory and the consequent effects for the population of Cachoeira do Sul, especially as regards the changes occurred in the productive chains with the replacement of the grains and livestock by sugar-cane and the new relations between capital and labor. From the readings taken in theoretical compiled, in lifting of secondary data and field research with achievement of interview, simple observation, confection of the field diary and photographic record, we found that the territorial configuration of Cachoeira Dourada in the beginning of XXI century is undergoing a process of transformation , spurred by the subjects of the sugar cane industry . We are therefore facing a hegemonic process that aims to develop a monopoly on the use of the territory by ethanol and energy production. From the new relations established in the municipality, is the crop conversion process, through its inclusion within the sugarcane.
Territorialization the sugar cane agroindustry in Cachoeira Dourada (GO) ande the sócio-spatial transformations
Keywords: Territorialização da agroindústria canavieira; Monopolização do território; Efeitos socioespaciais; Cachoeira Dourada (GO); Territorialization of the sugarcane agroindustry; Monopolization of the territory; Socio-spatial effects; Cachoeira Dourada (GO); CIENCIAS HUMANAS::GEOGRAFIA